A power quality enhanced for the wind turbine with sensorless direct power control under different input voltage conditions - Z.E.Z. Laggoun; H. Benalla; K. Nebti (Electrical engineering & Electromechanics, 2021)
Introduction. The quality of electrical energy is essential during disturbances, at the level of power electronic devices will suffer serious operating problems causing dangerous damage. Aim. A new approach to direct power control without grid voltage sensor improves the quality and control of instantaneous active and reactive power converters. Methodology. First, the technique without network voltage sensor with a direct power control based on a switching table, which is a classic approach, is discussed and its performance is analyzed under increasing and decreasing load. In addition, the performance of the proposed technique is also analyzed under the same circumstances and their performance is compared. Originality. The new method consists of a nonlinear grid voltage modulated controller and a conventional controller which guarantees very good results in a polluted network. The proposed method is verified using MATLAB/Simulink. Results. The simulation results under different input voltage conditions show that the proposed method not only has good tracking performance in active and reactive power, but also reduces the current total harmonic distortion to 1.9 %, which is good lower than the requirement for network operation.